CORRELATION OF SALIVARY TESTOSTERONE LEVELS WITH EXTROVERTED PERSONALITY IN STUDENTS OF THE FACULTY OF MEDICINE JENDERAL SOEDIRMAN UNIVERSITY - Ahmad Firdaus Firman Maulana; Mustofa Mustofa; Khusnul Muflikhah (Fakultas Kedokteran Universitas Jenderal Soedirman, 2022)
Testosterone is the main male sex hormone produced by Leydig cells in the testis. Measurement of testosterone levels can use saliva samples. Testosterone has many roles in reproductive and non-reproductive functions, such as behavior. Behavior includes aggressive and dominant traits. Aggressive behavior has a relationship with extrovert personality. This study aims to determine the correlation of salivary testosterone levels with extroverted personality in students of the Faculty of Medicine Jenderal Soedirman University. This study is observational with a cross-sectional study design. The number of subjects in this study was 26 students taken with consecutive sampling, with inclusion criteria of male aged 17-25 years, agreed to informed consent, BMI 18-24,9 kg/m2, didn’t smoke, and didn’t consume alcohol. Testosterone level was measured with a Salimetrics ELISA kit. Measurement of extrovert personality using the MBTI questionnaire. The normality test of the data used the Saphiro-Wilk test and bivariate analysis using the Pearson correlative parametric test. The results of measurements on the subjects obtained salivary testosterone levels 11,64±2,51 pg/mL and extrovert personality 41,02±19,74 %. The results of the Pearson correlation test salivary testosterone with extroverted personality values obtained p = 0,007 and r = 0,517 which means that there is a significant correlation between salivary testosterone levels and extrovert personality. The conclusion of this study is there is a correlation between salivary testosterone levels and extrovert personality in students of the Faculty of Medicine Jenderal Soedirman University.